Timing of respiratory syncytial virus and influenza epidemic activity in five regions of Argentina, 2007‐2016. Issue 1 (20th November 2018) - Baumeister, Elsa; Duque, Jazmin; Varela, Teresa; Palekar, Rakhee; Couto, Paula; Savy, Vilma; Giovacchini, Carlos; Haynes, Amber K.; Rha, Brian; Arriola, Carmen S.; Gerber, Susan I.; Azziz–Baumgartner, Eduardo
Abstract : Background: Within‐country differences in the timing of RSV and influenza epidemics have not been assessed in Argentina, the eighth largest country in the world by area. Objective: We aimed to compare seasonality for RSV and influenza both nationally and in each of the five regions to inform Argentina's prevention and treatment guidelines. Method: The Argentine National Laboratories and Health Institutes Administration collected respiratory specimens from clinical practices, outbreak investigations, and respiratory virus surveillance in 2007‐2016; these were tested using immunofluorescence or RT‐PCR techniques. We calculated weekly percent positive (PP) and defined season onset as >2 consecutive weeks when PP exceeded the annual mean for the respective year and region. Median season measures (onset, offset and peak) and the established mean method were calculated for each virus. Results: An annual median 59 396 specimens were tested for RSV and 60 931 for influenza; 21–29% tested positive for RSV and 2–7% for influenza. National RSV activity began in April; region‐specific start weeks varied by 7 weeks. Duration of RSV activity did not vary widely by region (16–18 weeks in duration). National influenza activity started in June; region‐specific start weeks varied by 3 weeks. Duration of influenza epidemic activity varied more by region than that of RSV (7–13 weeks in duration). Conclusion: In Argentina, RSV and influenza activity overlapped during the winter months. RSV season tended to begin prior to the influenza season, and showed more variation in start week by region. Influenza seasons tended to vary more in duration than RSV seasons.